Some L^s Inequalities for Polynomials not Vanishing Inside a Circle: Abdullah Mir, Bilal Dar - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we establish some L^s-inequalities for polynomials not vanishing inside a circle, from which a variety of interesting results follows as special cases.